Utilization of phosphogypsum from industrial dumps as an element of environmentally safe energy- and resourceconserving technologies - Pikarenia, Dmytro; Пікареня, Дмитро; Orlinska, Olha; Орлінська, Ольга; Hapich, Hennadii; Гапіч, Геннадій; Rudakov, Leonid; Рудаков, Леонід; Chushkina, Iryna; Чушкіна, Ірина; Mazurenko, Roman; Мазуренко, Роман (My University, 2024)
The paper discusses the problem of disposal and processing of phosphogypsum dumps as an element of environmentally safe energy- and resource- conserving technologies. The process of impact and possibility of phosphogypsum pre-treatment with weak electric fields to improve its physical and mechanical properties was studied. Two samples of different origin phosphogypsum, which are located in dumps on the territory of the Kamianske City (Ukraine), were used as research material. The research was conducted on samples of the following fractions: 1.0–2.0, 0.4–1.0, 0.1–0.4 mm. Further, balls were formed from the treated phosphogypsum and raw materials to study their compressive strength. The experiment was performed on a pellet strength meter, which operates in the range of 0–2.5 kgf/grain. Phosphogypsum balls, treated with electric current, did not collapse with the maximum values of the device. According to the research results, it was established that preliminary treatment with a low electric current leads to a decrease in the dehydration temperature of phosphogypsum, and the subsequent hydration allows to obtain a material with higher compressive strength properties. This substantiates the potential possibility of involving research results to obtain a cheaper product and will allow to liquidate multiton deposits of phosphogypsum. У статті розглядається проблема утилізації та переробки відвалів фосфогіпсу як елемента екологічно безпечних енерго- та ресурсозберігаючих технологій. Досліджено процес впливу та можливість попередньої обробки фосфогіпсу слабкими електричними полями для покращення його фізико-механічних властивостей. Як дослідницький матеріал використано дві проби фосфогіпсу різного походження, які знаходяться у відвалах на території м. Кам'янське (Україна). Дослідження проводили на зразках фракцій: 1,0–2,0, 0,4–1,0, 0,1–0,4 мм. Далі з обробленого фосфогіпсу та сировини формували кулі для вивчення їх міцності на стиск. Експеримент проводили на силомірі окатишів, який працює в діапазоні 0–2,5 кгс/гран. Фосфогіпсові кульки, оброблені електричним струмом, не руйнувалися при максимальних значеннях приладу. За результатами досліджень встановлено, що попередня обробка слабким електричним струмом призводить до зниження температури дегідратації фосфогіпсу, а подальша гідратація дозволяє отримати матеріал з більш високими властивостями міцності на стиск. Це обґрунтовує потенційну можливість залучення результатів досліджень для отримання більш дешевої продукції та дозволить ліквідувати багатотонні поклади фосфогіпсу.
Утилізація фосфогіпсу промислових відвалів як елемент екологічно безпечних енерго- та ресурсозберігаючих технологій
Keywords: phosphogypsum; фосфогіпс; landfills; відвали; utilization; утилізація; energy; енергетика